Recommendations for specific breeds and species for conservation by management and preferred techniques - Adeniji, K.O. (Food and Agriculture Organization of the United Nations, 1984)
In Africa, the only avenue to conserve a breed endangered is in the living form since techniques for storage of embryos have not yet been adequately developed. Furthermore, most countries might not be able to meet the financial involvement of such a programme. This is why it is highly recommended that multiplication and breeding centers should be established for the endangered breeds of Africa. In cases where governments are unable to finance such centres, international organizations and donor agencies could be approached for aid in funding these centres. A case in point is the African Development Bank which is financing the conservation effort on the Lagune breed in the Republic of Benin. It is also recommended that pure bred herds of the endangered breeds of high potential e.g. the Butana, Kenana, Kuri, and Mpwapwa should be established with the aim of exporting males. The foreign exchanges generated will help in maintaining the centres. In countries where there are no breeding programmes and policies, efforts must be made to develop one in order for conservation measures to have a lasting effect. It is also not out of place to suggest the formation of breeding and breed societies at national level to coordinate livestock production efforts in the country.